System Quality, Perceived Value, Brand Personality, dan User Engagement untuk memprediksi Behavioral to Subscribe Pelanggan Layanan Online Streaming - Yohanes Nuhadriel; Keni Keni (Jurnal Bisnis dan Akuntansi, 2022)
Technology has become the industry that has the most influence on the national and global economy. Along with the increasing growth of internet users due to the Covid-19 pandemic, has increased the level of competition in the online streaming service industry is getting higher, Furthermore to increase competitive advantage and business continuity, online streaming services need to increase the level of loyalty to subscribe. This study aims to empirically test 1) system quality, perceived value, and brand personality on subscription behavior. 2) system quality and perceived value of user interaction. 3) user interaction on behavior to subscribe. 4) system quality and perceived value towards subscriber behavior through user interaction. The research hypothesis was tested using PLS-SEM to 163 respondents, namely online streaming service customers. The results showed that only system quality could not predict behavior to subscribe directly, while all other variables were able to predict behavioral to subscribe.